Prophage WO Genes Recapitulate and Enhance Wolbachia-induced Cytoplasmic Incompatibility - LePage, Daniel P. (Nature, 2017)
The genus Wolbachia is an archetype of maternally inherited intracellular bacteria that infect the germline of numerous invertebrate species worldwide. They can selfishly alter arthropod sex ratios and reproductive strategies to increase the proportion of the infected matriline in the population. The most common reproductive manipulation is cytoplasmic incompatibility (CI), which results in embryonic lethality in crosses between infected males and uninfected females. Females infected with the same Wolbachia strain rescue this lethality. Despite more than 40 years of research(1) and relevance to symbiont-induced speciation(2,3), as well as control of arbovirus vectors(4,5,6) and agricultural pests(7), the bacterial genes underlying CI remain unknown. Here, we use comparative and transgenic approaches to demonstrate that two differentially transcribed, codiverging genes in the eukaryotic association module of prophage WO(8) from Wolbachia strain wMel recapitulate and enhance CI. Dual expression in transgenic, uninfected males of Drosophila melanogaster crossed to uninfected females causes embryonic lethality. Each gene additively augments embryonic lethality in infected males crossed to uninfected females. Lethality associates with embryonic defects that parallel those of wild type CI and is notably rescued by wMel-infected embryos in all cases. The discovery of cytoplasmic incompatibility factor genes cifA and cifB pioneers genetic studies of prophage WO-induced reproductive manipulations and informs Wolbachia’s ongoing utility to control dengue and Zika transmission to humans.